Analysis of Factors That Influence the Provincial Minimum Wage in SUMBAGSEL - Muhammad Afif Alpino; Muhammad Rusdi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research plans to look for the influence of the SUMBAGSEL Province Minimum Wage variable from 2015 to 2022. For this examination, the Fixed Effect Model (FEM) panel data is investigated. For this research, we used secondary data (time series) from 2015–2022. Apart from that, we used cross section data from five provinces in SUMBAGSEL, namely Bengkulu, Lampung, South Sumatra, Jambi and the Bangka Belitung Islands. We also used the EVIEWS version 12 program. This test shows that the Gross Regional Domestic Product variable has a significant positive effect on the Provincial Minimum Wage in SUMBAGSEL, Per Capita Consumption does not have a significant effect on the Provincial Minimum Wage in SUMBAGSEL, and the inflation and CPI variables have a significant negative effect. at the Provincial Minimum Wage in SUMBAGSEL